2014
DOI: 10.1186/1869-5760-4-5
|View full text |Cite
|
Sign up to set email alerts
|

Endophthalmitis after open globe injuries: changes in microbiological spectrum and isolate susceptibility patterns over 14 years

Abstract: BackgroundThe objective of this study was to evaluate the microbiologic spectrum and antimicrobial susceptibility of isolates in post-traumatic endophthalmitis and compare with our earlier published report. A retrospective review was conducted on 581 consecutive patients with culture-proven post-traumatic endophthalmitis at L. V. Prasad Eye Institute, India, from January 2006 to March 2013.FindingsA total of 620 isolates from 581 patients were identified (565 bacteria and 55 fungi). The most common isolate was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 6 publications
4
30
0
1
Order By: Relevance
“…16 The relatively higher frequency of fungi might be associated with open-globe injuries involving vegetable matter or soil contamination due to the mild and moist climate in our series. 17 There was also a relatively high incidence of B. cereus, which is known to be highly virulent and to cause rapid progression to panophthalmitis, [18][19][20] which might be associated with open-globe injuries with intraocular foreign bodies, particularly metal objects and the variety of trauma causes in our series. To optimize the prevention of endophthalmitis using prophylactic antibiotics, it is imperative to understand which antimicrobial regimen will be effective against the possible causative organisms.…”
Section: Discussionmentioning
confidence: 87%
“…16 The relatively higher frequency of fungi might be associated with open-globe injuries involving vegetable matter or soil contamination due to the mild and moist climate in our series. 17 There was also a relatively high incidence of B. cereus, which is known to be highly virulent and to cause rapid progression to panophthalmitis, [18][19][20] which might be associated with open-globe injuries with intraocular foreign bodies, particularly metal objects and the variety of trauma causes in our series. To optimize the prevention of endophthalmitis using prophylactic antibiotics, it is imperative to understand which antimicrobial regimen will be effective against the possible causative organisms.…”
Section: Discussionmentioning
confidence: 87%
“…Jindal et al have reported 32/65 (49 %) GNB isolates from patients with acute onset post-operative endophthalmitis are resistant to ceftazidime [15]. The same groups of authors have reported 22 % of GNB isolated from patients with open globe injuries are resistant to ceftazidime [16]. Anand et al reported 38 % of GNB isolates from patients with post-operative endophthalmitis are resistant to ceftazidime [17].…”
Section: Discussionmentioning
confidence: 95%
“… 108 , 109 Gram-positive cocci are the more common isolates among bacteria, followed by Gram-positive bacilli and other Gram-negative organisms. 108 , 109 Among Gram-positive cocci, coagulase-negative Staphylococcal organisms (ie, S. epidermidis and Staphyloccoccus saprophyticus ) along with Streptococcus species are the predominant groups. Gram-positive Bacillus species have been commonly reported in culture isolates of posttraumatic endophthalmitis.…”
Section: Classification Of Endophthalmitismentioning
confidence: 99%